Habitat stability and interspecific associations among invertebrate assemblages in New Zealand streams - Russell G. Death (New Zealand Journal of Marine and Freshwater Research, 2000)
To explore whether biotic interactions may be more common in benthic invertebrate communities in stable compared with unstable New Zealand streams, interspecific associations of invertebrate stone assemblages were examined in 10 streams of similar geomorphological character but differing stability. More significant correlations were found than expected by chance at most sites. Stable sites had more negative and positive associations than the unstable sites, although in most instances there were similar numbers of positive and negative correlations. The variance ratio test indicated an overall positive association when all taxa were considered. However, negative associations occurred between a significant number of taxa and were more common at stable sites. Although it remains to be seen whether the negative associations are a result of competition, it does seem biotic interactions are more common in the stable streams than in the flood prone ones as predicted by the harsh‐benign hypothesis.